Patterns Of Teacher And Student Communication In The Learning Process At Sma Negeri 20 MoramoSouth Konawe District - Larisu, Zulfiah; Darnawati, Darnawati; Jopang, Jopang; Irwan, Irwan (PT. Anagata Sembagi Education, 2024)
Communication is the key in the world of education, which is quite determinant in achieving goals. A teacher, no matter how clever and knowledgeable he is, if he is, will certainly not be able to provide a transformation of his knowledge to his students. This research aimed to analyze communication patterns between teachers and students in the learning process at SMAN 20 Moramo. This research used qualitative research methods with research subjects, namely teachers and students who were actively learning and teaching. Field data collection used observation, interview, and literature study techniques. Data processing involved data reduction, data display, and data verification, so that research results could be found. The research results showed that the dominant communication pattern was two-way communication, teachers and students provide information to each other, starting with the teacher as a source of information.